Molecular Interaction and Synergistic Activation of a Promoter by Six, Eya, and Dach Proteins Mediated through CREB Binding Protein - Ikeda, Keiko (American Society for Microbiology, 2002)
Drosophila sine oculis, eyes absent, and dachshund are essential for compound eye formation and form a gene network with direct protein interaction and genetic regulation. The vertebrate homologues of these genes, Six, Eya, and Dach, also form a similar genetic network during muscle formation. To elucidate the molecular mechanism underlying the network among Six, Eya, and Dach, we examined the molecular interactions among the encoded proteins. Eya interacted directly with Six but never with Dach. Dach transactivated a multimerized GAL4 reporter gene by coproduction of GAL4-Eya fusion proteins. Transactivation by Eya and Dach was repressed by overexpression of VP16 or E1A but not by E1A mutation, which is defective for CREB binding protein (CBP) binding. Recruitment of CBP to the immobilized chromatin DNA template was dependent on FLAG-Dach and GAL4-Eya3. These results indicate that CBP is a mediator of the interaction between Eya and Dach. Contrary to our expectations, Dach binds to chromatin DNA by itself, not being tethered by GAL4-Eya3. Dach also binds to naked DNA with lower affinity. The conserved DD1 domain is responsible for binding to DNA. Transactivation was also observed by coproduction of GAL4-Six, Eya, and Dach, indicating that Eya and Dach synergy is relevant when Eya is tethered to DNA through Six protein. Our results demonstrated that synergy is mediated through direct interaction of Six-Eya and through the interaction of Eya-Dach with CBP and explain the molecular basis for the genetic interactions among Six, Eya, and Dach. This work provides fundamental information on the role and the mechanism of action of this gene cassette in tissue differentiation and organogenesis.